Dogs and cats - Jenkins, Steve, 1952- (Houghton Mifflin Co., 2007)
"Are you a cat lover? A dog person? Either way, this book is for you! Read about how your favorite companion came to be a pet and how its body works. Then, flip the book over and find out about the other kind."--barnesandnoble.com